Adaptive decentralised control of fluid networks with random disturbances - Zhu, Song; Wang, Min; Liu, Yingke (IET control theory & applications, 2017)
This study is devoted to control of fluid networks subject to random disturbance. Adopting stochastic differential equation theory, an improved model is presented to incorporate not only the non-linearities induced by fan branch but also random disturbances. On the basis of the model, combining decentralised control and adaptive control techniques, the mean square exponential stability is proposed. According to the proposed stability, the desired equilibrium of fluid flows could be ensured by setting controllers just related to links. Two engineering examples are provided to show the effectiveness of the proposed method.